Homogeneous Hydrogenation of CO2 and CO to Methanol: The Renaissance of Low‐Temperature Catalysis in the Context of the Methanol Economy. (14th September 2022) - Sen, Raktim; Goeppert, Alain; Surya Prakash, G. K.
Abstract: The traditional economy based on carbon‐intensive fuels and materials has led to an exponential rise in anthropogenic CO2 emissions. Outpacing the natural carbon cycle, atmospheric CO2 levels increased by 50 % since the pre‐industrial age and can be directly linked to global warming. Being at the core of the proposed methanol economy pioneered by the late George A. Olah, the chemical recycling of CO2 to produce methanol, a green fuel and feedstock, is a prime channel to achieve carbon neutrality. In this direction, homogeneous catalytic systems have lately been a major focus for methanol synthesis from CO2, CO and their derivatives as potential low‐temperature alternatives to the commercial processes. This Review provides an account of this rapidly growing field over the past decade, since its resurgence in 2011. Based on the critical assessment of the progress thus far, the present key challenges in this field have been highlighted and potential directions have been suggested for practically viable applications. Abstract : Production of renewable methanol using recycled CO2 and green H2 is a long‐term solution to address the carbon conundrum and achieve a sustainable economy. This Review reflects on the key developments in low‐temperature methanol synthesis from CO2 and CO using homogeneous catalysts. The integration of direct air capture of CO2 and its conversion to methanol as a promising avenue in "air‐to‐fuel" technologies is also highlighted.